Prognostic Significance of Lymphovascular Space Invasion in Epithelial Ovarian Cancer - Chen, Ming (J Cancer, 2015)
Object: To assess the effects of lymphovascular space invasion (LVSI) on cancer recurrence and survival in patients with primary epithelial ovarian cancer. Methods: A retrospective study was conducted of patients with stage I-IV primary epithelial ovarian cancer who underwent cytoreductive surgery. LVSI is defined as the presence of tumor cells within an endothelium-lined space, and the patients' pathologic slides were reevaluated by gynecological pathologists. Survival analysis was performed to compare risk factors. Results: A total of 492 patients were included in the analysis. The incidence of LVSI was 58.5% in our cohort (288 cases), and it was significantly associated with advanced stage, high-grade serous histology, high grade, and lymph node metastasis (P<0.001). Kaplan-Meier analysis demonstrated that LVSI was only correlated with decreased PFS (5-year rate, 39% vs. 66%, P<0.001) and OS (5-year rate, 44% vs. 78%, P<0.001) in patients at early stage but not at advanced stage (5-year rate, PFS: 14% vs. 11%, P<0.001; OS: 29% vs. 29%, P=0.141). Multivariate analysis showed that LVSI remained a significant variable with PFS and OS in early-stage ovarian cancer (PFS: HR 2.29, 95% CI 1.45-3.57; OS: HR 2.20, 95% CI 1.59-3.44, both P<0.001). Conclusion: LVSI is an independent predictor of progression and survival in patients with primary epithelial ovarian cancer at early stage but not at advanced stage.